Law Enforcement Of Giving Restitution For Victims Of Trafficking In The State Court Of Central Jakarta - Roswati Dewi; Sri Endah Wahyuningsih; Umar Ma'ruf (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
This study aimed to analyze and assess: 1) Law Enforcement of Giving Restitution of Victim of Crime Against Trafficking in West Java Police Jurisdiction; 2) obstacles and barriers in the Restitution Administration of the Victim of Crime Against Trafficking in West Java Police Jurisdiction; and 3) How to overcome the obstacles in Giving Restitution of Victim of Crime Against Trafficking in West Java Police Jurisdiction.This research use sociological juridical approach to the specification of the research is descriptive analysis. Data sources include primary data and secondary data. Methods of data collection using interviews and documentation study. Methods of data analysis in this thesis using qualitative descriptiveThe study concluded that not every Victims of Crime of Trafficking Got Giving Restitution. Obstacles Giving Victims Restitution against Crime of Trafficking affected by the dominant legal factors and the influence of other factors. UUPTPPO an attempt by the State to TPPO, but construction is still weak, law making it difficult for victims obtain restitution, so it needs to be revised. It is recommended that UUPTTPO revised or reconstructed, so UUPTPPO for more providing legal protection for victims of TPPO to establish in the regulations (laws) that the State through the investigating police and / or prosecutor (JPU) who shall seek fulfillment TPPO restitution by offenders to victims TPPO, that is the nation participation for the society.Keywords: Law Enforcement; Restitution; Victims; Crime; Trafficking.